2020
DOI: 10.1111/tid.13390
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative intensive glycemic control for liver transplant recipients to prevent surgical site infection: A systematic review and meta‐analysis

Abstract: Liver transplantation is indicated for patients affected by end-stage liver diseases. 1 However, transplant supply does not meet the demand. In 2019, only 65% of the 12 708 patients on the national waiting list in the US received a transplant after waiting an average of 3.7 years. 2,3 Liver transplantation is also an expensive procedure with costs ranging from US$ 145 277 to US$ 181 598. 4 Given the scarcity of transplants, a transplant which then fails to take is especially distressing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Thus, the higher risk of SSI in these patients is not unexpected. 26 Similar to other studies, we found an increased risk of SSI with posttransplant procedures 9,16 and longer operative times as has been, 4,27,28 which likely reflects increased opportunity for wound contamination, increased inflammation, and delayed healing. There may be some variability in surgical techniques that can potentially influence the rate of SSI.…”
Section: Discussionsupporting
confidence: 87%
“…Thus, the higher risk of SSI in these patients is not unexpected. 26 Similar to other studies, we found an increased risk of SSI with posttransplant procedures 9,16 and longer operative times as has been, 4,27,28 which likely reflects increased opportunity for wound contamination, increased inflammation, and delayed healing. There may be some variability in surgical techniques that can potentially influence the rate of SSI.…”
Section: Discussionsupporting
confidence: 87%
“…A recent literature review highlighted the lack of prospective studies evaluating the outcome of intensive blood glucose control among liver transplant recipients on SSI incidence and called for more high quality trials on this topic [13]. This paper describes a clinical randomized trial designed to test the hypothesis that post-operative intensive blood glucose control reduces the incidence of SSI among liver transplant recipients.…”
Section: Introductionmentioning
confidence: 99%